Cellulose carboxylate/tosylate mixed esters: Synthesis, properties and shaping into microspheres. (5th November 2016) - Ferreira, Daniela C.; Bastos, Gustavo S.; Pfeifer, Annett; Heinze, Thomas; El Seoud, Omar A.
Highlights: Cellulose carboxylates/tosylate (acetate/butanoate/hexanoate) were synthesized. Determination of degree of substitution DSCarboxy by FTIR and UV–vis was studied. The IR peak area and frequency (CO and SO) depend linearly on DSCarboxy . Empirical polarity of ester films depend linearly on DSCarboxy . These mixed cellulose esters were shaped into homogeneous nanospheres. Abstract: Cellulose carboxylate/tosylate mixed esters (Cel-Carboxy/Ts) were synthesized with constant degree of tosylation, DSTs  = 0.98 and variable degree of acylation, DSCarboxy ; acetate, butanoate, and hexanoate. The tosylate (Cel-Ts) was prepared by reacting cellulose with tosyl chloride in presence of trimethylamine. The mixed esters were obtained by reacting Cel-Ts with carboxylic acid anhydride. The dependence of the following on DSCarboxy was investigated: IR data, including ν CO, ν SO and peak area (CO); empirical polarity of the films, determined by an adsorbed perichromic dye. We employed these parameters to determine DSCarboxy . Relative to ester saponification, these spectroscopic methods are convenient, expedient, and require much less sample. Mixed esters prepared physically from cellulose tosylate and tosylate/acetate behave only qualitatively similar to (Cel-Carboxy/Ts). The mixed esters were dissolved in acetone and regenerated in water as homogeneous microspheres.